Rainfall interception by thorn scrub forest in Atotonilco el Grande, Hidalgo - Flores Ayala, Eulogio; Becerra Luna, Francisco; Buendía Rodríguez, Enrique; Carrillo Anzures, Fernando; Terrazas Gonzáles, Gerardo H.; Pineda Ojeda, Tomás; Acosta Mireles, Miguel (Revista Mexicana de Ciencias Agrícolas, 2018)
Interception of rain is the process by which rainwater modifies its trajectory to be intercepted by the canopy, thereby exerting a marked influence on the pattern of the rain that makes it to the forest floor. Once intercepted, the water is retained by the leaves and branches of trees, including epiphytes, making from now, its trajectory by one or more of these three ways: evaporation, dripping from the top, or flow through the branches to the base of the stem (García, 2006). Interception studies are one of the ways that identify how the current conditions in tree cover, or changes to this structural condition, affect the water balance of a wooded area, either by the application of silvicultural techniques or natural disturbances. In the case of Mexico, this research area has been moderately exploredinparticularinthefieldofecology.Theobjective of this study is to quantify the interception of rain and its variability, measured under canopy in stands whose dominant vegetation is Acacia farnesiana and Juniperus f laccida. In a forest area of the municipality of Atotonilco el Grande, Hidalgo; it was established a research module of 0.64 ha, where 60 rain gauges were placed under the canopy of a forest area representative, formed by different species and degrees of canopy cover and an irregular topography. The study covered the entire rainy seasonof2007.Asaresult,itwasdeterminedanaverage interception of 18.6%, finding a great variability, both between and within rain events. Is reported a statistical relationship between the logarithmic type between interception percentage and total amount of precipitation by event. We found no statistical relationship between the interceptions with the irregular topography. We conclude on the need to extend the analysis to assess the contribution of site variables and vegetation.
Keywords: Acacia farnesiana (L.) Willd; Eysenhardtia polystachya (Ortega) Sarg.; Juniperus f laccida Schltdl. var. Flaccida; canopy; stemflow; interception of rain; throughfall